Kajian Pengembangan Desa Wisata Jontor Subulussalam Sebagai Dasar Perancangan Paket Wisata - Alidha, Seprina Yana (Jurnal Serambi Engineering, 2025)
Tourism development, especially through the concept of tourist villages, is a crucial effort in sustainable development that directly involves the community. These problems arise due to limited understanding of managers in packaging potential and managing tourism. This study focuses on Jontor Village, Subulussalam City, which has natural and cultural wealth but has not been optimally managed, resulting in minimal tourist attractions. In addition, there are obstacles in community understanding of tourism businesses and collaboration between stakeholders. The main objective of this study is to map the potential of tourist villages in Jontor Village as a basis for designing tour packages. In addition, it will also identify the structure of the Tourism working group that has been formed, to support the management of tourist attractions and the sustainability of community livelihoods. This study will identify the potential and problems in Jontor Village, and formulate a tourist village development plan based on aspects of conservation, education, community involvement, local economy, and tourism. The method used is qualitative, through observation, interviews, and literature studies, to produce comprehensive, valid, and objective data.